2008
DOI: 10.1007/s11064-008-9808-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage and Cognitive Dysfunction: Antioxidant Treatments to Promote Healthy Brain Aging

Abstract: Oxidative damage in the brain may lead to cognitive impairments in aged humans. Further, in age-associated neurodegenerative disease, oxidative damage may be exacerbated and associated with additional neuropathology. Epidemiological studies in humans show both positive and negative effects of the use of antioxidant supplements on healthy cognitive aging and on the risk of developing Alzheimer disease (AD). This contrasts with consistent behavioral improvements in aged rodent models. In a higher mammalian model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 144 publications
(139 reference statements)
3
80
0
1
Order By: Relevance
“…The fact that acute application of vitamin C and trolox in vitro could not reverse aging-associated impairment of NMDAR-dependent LTP in rat hippocampus in this study suggests that administration of antioxidants, which can reduce ROS generation but not reverse oxidative inactivation of key functional macromolecules directly, has little acute effect on aging-related deficits in synaptic plasticity. In fact, most of the previous studies have indicated that chronic administration of antioxidants for a longer period of time could attenuate aging-related cognitive disorders (Clausen et al;Fukui et al, 2002;Head, 2009), suggesting that antioxidants might have a beneficial effect against brain aging if administered chronically. Considering the accumulation of oxidative damage as a long-term and continuous process, the protection of antioxidants by scavenging ROS might be a long-time result and preventive effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that acute application of vitamin C and trolox in vitro could not reverse aging-associated impairment of NMDAR-dependent LTP in rat hippocampus in this study suggests that administration of antioxidants, which can reduce ROS generation but not reverse oxidative inactivation of key functional macromolecules directly, has little acute effect on aging-related deficits in synaptic plasticity. In fact, most of the previous studies have indicated that chronic administration of antioxidants for a longer period of time could attenuate aging-related cognitive disorders (Clausen et al;Fukui et al, 2002;Head, 2009), suggesting that antioxidants might have a beneficial effect against brain aging if administered chronically. Considering the accumulation of oxidative damage as a long-term and continuous process, the protection of antioxidants by scavenging ROS might be a long-time result and preventive effect.…”
Section: Discussionmentioning
confidence: 99%
“…6C,D), suggesting that the difference may be attributed to the reduction of protein-bound thiol oxidation, not the scavenging of oxygen free radicals. Previous studies have illuminated that chronic administration of antioxidants could attenuate aging-related cognitive disorders (Clausen et al ;Fukui et al, 2002;Head, 2009). However, this study did not show any acute effect of antioxidants on LTP impairment of aged rats.…”
Section: Antioxidant Prevents But Reductant Reverses H 2 O 2 -Inducementioning
confidence: 99%
“…However, hyperglycaemia, as may occur, for example, after a high-GI meal, is also associated with several other physiological conditions with potential negative impact on the brain; for example, increased oxidative stress, 32,33 increased inflammatory markers (IL-6) 34,35 and increased cortisol concentrations. 36 In addition, acute hyperglycaemia in normal subjects may result in vasoconstriction.…”
mentioning
confidence: 99%
“…There is evidence that dietary enrichment with nutritional antioxidants could improve brain damage and cognitive function (Bisson et al, 2008;Head, 2009). Zingiber officinale Roscoe (Zingiberaceae) or ginger is widely used as a spice.…”
Section: Introductionmentioning
confidence: 99%